Coraline : The Graphic novel - Gaiman, Neil (HarperCollins, 2008)
Coraline, who lives with her parents and some other people in a strange old house, explores the garden, grounds and eventually the inside of the mansion, where a door leads her to another universe that darkly mirrors the one she arrived from. Graphic novel adaptation.